Healthy Connections: Crafting Compelling Healthcare Marketing Strategies - El Khair, Riat; Aini, Qurratul (Scripta Medica, 2024)
Due to the importance of healthcare on both an individual and public level, the efficient functionality of the healthcare system is a fundamental component of society’s overall well-being. The primary purpose of this research was to assess how academic contributions to healthcare marketing investigations have evolved over time. The paper delved into various aspects from 2015 to 2024, including publishing trends, core journals, authorship patterns, institutional affiliations, nation-wise contributions, theme distributions, author collaborations and keywords. Data was collected from the Scopus database by using appropriate keywords. The collected dataset underwent meticulous analysis and visualisation using the VOSviewer software. This analytical approach facilitated the identification of significant bibliometric metrics, enabling a deeper understanding of the dynamics and peculiarities of healthcare marketing research throughout the specified period. The most fruitful affiliation or institutional source for healthcare marketing was University Sains Malaysia. Top 5 most productive authors contributing to the field of healthcare marketing were Bellio et al, Buccoliero et al, Djakeli et al, Ghinita et al and Harrison et al. The United States was the nation that produces the greatest number of scientific articles related to healthcare marketing. The most important journal for healthcare marketing was International Journal of Pharmaceutical and Healthcare Marketing. The most common subjects in healthcare marketing were business, management and accounting. With twenty-one publications, the number of international scholarly publications on healthcare marketing reached a peak in 2023. Eleven writers were closely associated with the ownership of two or more documents. There were 24 keywords with a significant human correlation.